2016
DOI: 10.1177/1545968316653836
|View full text |Cite
|
Sign up to set email alerts
|

Same Intervention–Different Reorganization

Abstract: Different patterns of change in activation are evident following touch discrimination training with thalamic/capsular lesions compared with S1/S2 cortical somatosensory lesions, despite common training and similar improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 55 publications
1
23
0
Order By: Relevance
“…At 14 days after stroke, our interregional and node degree analysis revealed that, compared to STD, EE increased RS-FC among these particular networks relevant for recovery of proprioception ( Ben-Shabat et al, 2015 ) and touch ( Carey et al, 2016 ) in stroke patients. We therefore propose that RS-FC changes observed in the secondary motor cortices, contralesional posterior parietal and retrosplenial regions could be instrumental in the marked improvements in tactile-proprioceptive function observed after stroke in the EE group.…”
Section: Discussionmentioning
confidence: 78%
“…At 14 days after stroke, our interregional and node degree analysis revealed that, compared to STD, EE increased RS-FC among these particular networks relevant for recovery of proprioception ( Ben-Shabat et al, 2015 ) and touch ( Carey et al, 2016 ) in stroke patients. We therefore propose that RS-FC changes observed in the secondary motor cortices, contralesional posterior parietal and retrosplenial regions could be instrumental in the marked improvements in tactile-proprioceptive function observed after stroke in the EE group.…”
Section: Discussionmentioning
confidence: 78%
“…These reductions could be indicative of network-level inefficiencies important for segregation. For example, in mice we have recently shown (59) that improved tactile proprioception after stroke was associated with increased node degree in motor, somatosensory, and parietal cortices -all regions relevant for processing proprioception and touch (60). In the present study, reduced within-network connectivity (i.e., node degree) combined with poorer integration across networks (i.e., reduced anticorrelations) could impair multidomain behavioral output, as demonstrated by poorer social and emotional performance of the OXT-treated group.…”
Section: Discussionmentioning
confidence: 99%
“…Age-related changes in activation have been seen, with decreased activation in S2 with tactile stimulation evident in elderly participants who are known to experience behavioral decline in somatosensory thresholds (54). The relationship of bilateral S2 with tactile sensation must also be considered in fields such as stroke research, where the location of the lesion has been demonstrated to impact both the type of somatosensory dysfunction (107), and also the ability to recover after stroke (108). Our finding of overlap in activation of right secondary somatosensory region for RH and LH tactile stimulation, may have particular relevance after stroke.…”
Section: Discussionmentioning
confidence: 99%